SAND PAINTING AS A STIMULATOR FOR DEVELOPMENT OF IMAGINATION AMONG JUNIOR SCHOOL CHILDREN - Khachibabyan , S. S.; Khanamiryan, I. R. (Modern Psychology, 2019)
This article focuses on the study of role of sand painting in the process of development of creativity. The article covers the course of an experiment conducted with the aim of development of creative qualities; the data and analysis thereof received as a result of study of one of the creative qualities, i.e. imagination; as well as the description of the sand painting project applied in the design stage of the experiment. The article is aimed at showing the role of sand painting in the process of development of creativity among junior schoolchildren upon analyzing such role within the context of peculiarities of the method.
Keywords: sand painting; creativity; creative qualities; development; imagination